Lumbopelvic alignment on standing lateral radiograph of adult volunteers and the classification in the sagittal alignment of lumbar spine - Pongsthorn Chanplakorn (2018)
The analysis of the sagittal balance is important for the understanding of the lumbopelvic biomechanics. Results from previous studies documented the correlation between sacro-pelvic orientation and lumbar lordosis and a uniqueness of spino-pelvic alignment in an individual person. This study was subjected to determine the lumbopelvic orientation using pelvic radius measurement technique. The standing lateral radiographs in a standardized standing position were taken from 100 healthy volunteers. The measurements which included hip axis (HA), pelvic radius (PR), pelvic angle (PA), pelvic morphology (PR-S1), sacral translation distance (HA-S1), total lumbosacral lordosis (T12-S1), total lumbopelvic lordosis (PR-T12) and regional lumbopelvic lordosis angles (PR-L2, PR-L4 and PR-L5) were carried out with two independent observers. The relationships between the parameters were as follows. PR-S1 demonstrated positive correlation to regional lumbopelvic lordosis and revealed negative correlation to T12-S1. PA showed negative correlation to PR-S1 and regional lumbopelvic lordosis, but revealed positive correlation to HA-S1. T12-S1 was significantly increased when PR-S1 was lesser than average (35°-45°) and was significantly decreased when PR-S1 was above the average. PR-L4 and PR-L5 were significantly reduced when PR-S1 was smaller than average and only PR-L5 was significantly increased when PR-S1 was above the average. In conclusion, this present study supports that lumbar spine and pelvis work together in order to maintain lumbopelvic balance. © 2010 Springer-Verlag.